A new Om(z) diagnostic of dark energy in general relativity theory - N. Myrzakulov; M. Koussour; Dhruba Jyoti Gogoi (European Physical Journal C: Particles and Fields, 2023)
Abstract In this paper, we propose a new parametrization of dark energy based on the Om(z) diagnostic tool behavior. For this purpose, we investigate a functional form of the Om(z) that predicts the popular dark energy dynamical models, namely phantom and quintessence. We also found the famous cosmological constant for specified values of the model’s parameters. We employed the Markov Chain Monte Carlo approach to constrain the cosmological model using Hubble, Pantheon samples, and BAO datasets. Finally, we used observational constraints to investigate the characteristics of dark energy evolution and compare our findings to cosmological predictions.